Pengaruh Minat Belajar dan Self-Regulated Learning terhadap Kemampuan Pemecahan Masalah Matematika Siswa Kelas X MA pada Materi SPLTV - Hidayah, Imroatul; Jamaluddin, Muhammad (Media Pendidikan Matematika, 2026)
Mathematics learning plays an important role in developing students' problem-solving abilities. However, many students still experience difficulties, resulting in low learning interest and hindering their ability to manage their learning process independently (self-regulated learning). This study aims to analyze the influence of learning interest and self-regulated learning on students' mathematical problem-solving abilities, both partially and simultaneously. This study used a quantitative approach with a non-experimental survey method on 53 class X students of MA Manbaul Ulum Mojopurogede. The research instruments were a learning interest questionnaire, a self-regulated learning questionnaire, and an essay test on mathematical problem-solving abilities. Data were analyzed using the Kolmogorov-Smirnov normality test, linearity test, and simple and multiple linear regression tests. The results showed that learning interest had a significant effect with a contribution of 38.3% (=0.383; p<0.05), while self-regulated learning provided a larger contribution of 42.7% (=0.427; p<0.05). Simultaneously, both variables contributed 48.7% (=0.487; p<0.05) to mathematical problem-solving ability, with self-regulated learning being the more dominant factor. Therefor, learning interest and self-regulated learning are important factors that need to be considered in efforts to improve students' mathematical problem-solving abilities.